Value of the 14-gene molecular assay in efficacy assessment of neoadjuvant chemoimmunotherapy for non-small cell lung cancer - Lan, Xuyan; Sun, Xiaoyu; Chen, Ruiqi; Zhu, Lihuan; Pan, Xiaojie; Guo, Tianxing (Frontiers in Molecular Biosciences, 2025)
ObjectiveTo evaluate the predictive accuracy of the 14-gene molecular assay in determining treatment response among patients with non-small cell lung cancer (NSCLC) undergoing neoadjuvant immunochemotherapy (nICT). Additionally, the study aims to investigate its correlation with tumor-infiltrating lymphocyte (TIL) levels and the status of tertiary lymphoid structures (TLS) in the tumor microenvironment.MethodsPatients with NSCLC who underwent nICT followed by surgical resection at Fuzhou University Affiliated Provincial Hospital between February 2019 and December 2022 were retrospectively included. Risk stratification was performed using the 14-gene quantitative PCR expression assay. The percentage of residual viable tumor cells (%RVT), TIL, and TLS within the primary lesion were evaluated through hematoxylin and eosin staining of surgical specimens. Subsequently, correlations were analyzed between the 14-gene molecular risk stratification and pathological response, as well as between the 14-gene molecular risk stratification and patient prognosis.ResultsA total of 114 patients were included. The pathological complete response (pCR) rate was significantly higher in the 14-gene low-risk group, while the RVT was notably lower (both P < 0.05). Additionally, the low-risk group showed significantly elevated levels of TIL and positivity for TLS (both P < 0.05). Survival analysis revealed that patients in the low-risk group had markedly longer disease-free survival (DFS) compared to those in the intermediate-risk and high-risk groups (both P < 0.05). Univariate Cox regression analysis identified pathological TNM stage, vascular invasion, pathological response, and 14-gene molecular risk stratification as significant factors influencing DFS (all P < 0.05). Furthermore, multivariate analysis confirmed that the 14-gene risk stratification was an independent prognostic factor for DFS (HR = 2.496, 95% CI: 1.264–4.931, P = 0.008).ConclusionThe 14-gene molecular assay demonstrated that low-risk status correlates with improved pathological response and prognosis, potentially attributable to higher TLS positivity rates and increased TIL infiltration. This assay offers critical insights for refining neoadjuvant treatment strategies in patients with NSCLC.